Tinjauan Kritis Terhadap Misi Penginjilan Paulus Terhadap Dinamika Kontemporer Dan Tantangan Dalam Masyarakat Modern - Jey Patandung (Jurnal Magistra, 2024)
This research uses a mixed approach to investigate the dynamics of Evangelical Missions in the context of modern society. By combining qualitative interviews, quantitative surveys, social media analysis, and focus groups, this research aims to understand how shifting social values and technology influence approaches to evangelism. Findings will provide a holistic view of the challenges and opportunities in conveying the Gospel message in the contemporary era. Literature studies support the theoretical foundation, while interviews and surveys involve active participation from various community groups. Social media content analysis reveals patterns in messaging, and focuses on providing groups with a platform to hear people's voices. It is hoped that the results of this research can provide a significant contribution to the practical and theoretical understanding of Evangelical Missions in an increasingly complex modern society.